SEXUAL EUPHEMISM EXPRESSED IN POP AND HIP HOP LYRIC SONGS: A PRAGMATIC STUDY - Cita Mustika Kusumah (English Journal Literacy Utama, 2019)
This research aims to describe and give an overview of the use of sexual euphemism in pop and hip hop lyric songs to avoid taboo words which are usually unfreely to mention in public. The researcher uses qualitative method and descriptive method to analyze the data. The researcher uses forty songs consist of twenty pop songs and twenty hip hop songs to be analysed. From forty songs, the researcher finds ninety seven data. Researcher believes the data are found to contain sexual euphemism in the utterance that included in pragmatic study.Researcher describes and analyzes every single of data that are included the theory of Allan and Buridge (1991). From the research data, the researcher found that there is a differential usage of sexual euphemism in pop and hip hop which is sexual euphemism in sexual activity appears more frequently in pop songs and sexual euphemism in sexual body parts appears more frequently in hip hop songs. Both pop and hip hop songs use representative speech act more frequently than directive speech act. Euphemism was used in the lyrics to avoid words that are considered taboo in some communities.Keywords: speech act, sexual euphemismINTRODUCTIONIn